Variable Levels of Resistance of Soybean Genotypes on the Performance of Euschistus heros (Hemiptera: Pentatomidae) - Souza, Efrain S.; Canassa, Vinicius F. [UNESP]; Bentivenha, Jose P. F.; Baldin, Edson L. L. [UNESP]; Pierozzi, Caroline G. [UNESP]; Lourencao, Andre L.; Pannuti, Luiz E. R. [UNESP] (Oxford Univ Press Inc, 2017)
The Neotropical brown stink bug Euschistus heros (Fabr.) (Hemiptera: Pentatomidae) is one of the major soybean pests in South America. This species is responsible for high levels of infestation, causes critical damage to seeds, it is associated with leaf retention on plants, and it is extremely difficult to manage. Host plant resistance is a notable technique to assist in reducing the stink bug population in soybean crops. The antibiosis resistance of soybean genotypes to E. heros was evaluated in laboratory. Genotypes L1-1-01, 'IAC 100', 'IAC 23', and 'Coodetec 208' increased the length of nymphal developmental time. PI 274453 and PI 227687 reduced egg viability and also adult body weight. PI 274454, 'IAC 19', PI 227687, and PI 229358 led to low nymphal viability. These results suggest that these genotypes may be useful in soybean breeding programs that focus on the development of genotypes resistant to E. heros.
Keywords: neotropical brown stink bug; host plant resistance; antibiosis; Glycine max